Evaluasi dalam Meningkatkan Hasil Permainan Bola Voly Melalui Bermain dengan Cara Melempar Bola - Deni Rahman Marpaung; Salman Rasyid Rangkuti; Rida Wahyuni; Aisyah Harahap; Claudia Caroline Zefanya Hasibuan; Noviola Sari Kusuma Sagala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research study is to determine the application of throwing the ball to improve the learning of passing volleyball in Class IV Medan students. The research uses a classroom action research design which is carried out in two cycles, each cycle consisting of planning, action implementation, observation and reflection. Research subject These are Class IV students, totaling 20 students. Data on volleyball learning outcomes were obtained through performance tests, observation sheets were used to collect data on student activities in following the volleyball learning process using the ball throwing method. The results of this research were obtained based on an assessment of three aspects, namely psychomotor, affective and cognitive. Regarding the national sports legislation system , sports development began to be taken seriously. The development of the club style was implemented in European countries, while the United States implemented the development of the school style. Volleyball has different characteristics and problems, so special treatment is needed to improve volleyball development optimally. Based on the statement that all systems will not be perfect, the two development paths above will be a challenge to choose the right one to implement. The development of volleyball in Indonesia is generally divided into clubs and education. Adapting two types of sports development will make the existence of a better volleyball development system.